Implementasi pengembangan kecerdasan emosional anak usia 5-6 tahun melalui prophetic parenting perspektif filsafat epistemologi - Nurfadlilah, Wuri Annisa; Suyadi, Suyadi; Diana, Raden Rachmy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2024)
The significant transformation of the 5.0 era presents challenges and opportunities, especially in the world of education. On the other hand, innovation in the development of information and technology requires adaptation, one of which is through emotional intelligence from an early age. The environment around children has an important role in developing children's emotional intelligence, both in the school environment and at home around children. The purpose of this study is to examine the application of developing children's emotional intelligence through prophetic parenting with an epistemological perspective at the Muslimat NU 001 Ponorogo Kindergarten. This research uses a type of qualitative method through a field study approach, with data collection techniques including three stages, namely observation, interviews, and documentation. The research sources consist of two subjects, namely primary sources including the results of field data and theories from books, as well as secondary sources from articles supporting this research. The analysis technique of the results of this study shows that the application of emotional intelligence in children includes seven characteristics of prophetic parenting, namely showing role models, finding the right time to give direction, being fair and equalizing gifts, fulfilling children's rights, buying children toys or rewards, helping children do obedience and filial piety, and not being angry and reproaching children. These activities are carried out through habituation and direction of children during learning hours and outside of learning, as well as monthly parenting activities with student guardians. This is in line with the point of view of epistemological philosophy which explains the origin, process, results and direction of knowledge as well as the concepts of “existence” and “existence” in education. The development of emotional intelligence through prophetic parenting at TK Muslimat NU 001 Ponorogo is very effective, systematic and recommended by the author as a reference for educators or parents in introducing and teaching emotional intelligence based on the Qur'an and Hadith.